Influence of Sudden Changes in Foot Strikes on Loading Rate Variability in Runners - Maxime Chabot; Alexandre Thibault-Piedboeuf; Marie-Lyne Nault; Jean-Sébastien Roy; Philippe C. Dixon; Martin Simoneau (Sensors)
Foot strike patterns influence vertical loading rates during running. Running retraining interventions often include switching to a new foot strike pattern. Sudden changes in the foot strike pattern may be uncomfortable and may lead to higher step-to-step variability. This study evaluated the effects of running with an imposed and usual foot strike on vertical loading rate variability and amplitude. Twenty-seven participants (16 men and 11 women; age range: 18–30 years) ran on an instrumented treadmill with their usual foot strike for 10 min. Then, the participants were instructed to run with an unusual foot strike for 6 min. We calculated the vertical instantaneous and vertical average loading rates and their variances over 200 steps to quantify vertical loading rate variability. We also calculated the amplitude and variability of the shank acceleration peak using an inertial measurement unit. The vertical loading rate and shank acceleration peak amplitudes were higher when running with a rearfoot strike, regardless of the foot strike conditions (i.e., usual or imposed). The vertical loading rate and shank acceleration peak variability were higher when running with an imposed rearfoot strike than when running with a usual forefoot strike. No differences were found in the vertical loading rate and shank acceleration peak variabilities between the imposed forefoot strike and usual rearfoot strike conditions. This study offers compelling evidence that adopting an imposed (i.e., unusual) rearfoot strike amplifies loading rate and shank acceleration peak variabilities.